2004
DOI: 10.1152/ajpheart.01212.2003
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in ANG II levels and action on multiple K+current modulation pathways in diabetic rats

Abstract: Gender differences were studied in ventricular myocytes from insulin-deficient (Type 1) diabetic rats. Cells were obtained by enzymatic dispersion of hearts from control male and female rats and from rats made diabetic with streptozotocin (100 mg/kg) 7–14 days before experiments. ANG II content, measured by ELISA, was augmented in diabetic males but unaltered in diabetic females. In diabetic ovariectomized females, ANG II levels were augmented as in males. ANG II affects multiple cellular pathways including ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
41
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 38 publications
5
41
0
Order By: Relevance
“…Estrogen has long been recognized as a suppressor of the RAS (11,25). Earlier work from our laboratory (43) showed that angiotensin II elevation is smaller in diabetic female hearts than in male hearts, concordant with the present results.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Estrogen has long been recognized as a suppressor of the RAS (11,25). Earlier work from our laboratory (43) showed that angiotensin II elevation is smaller in diabetic female hearts than in male hearts, concordant with the present results.…”
Section: Discussionsupporting
confidence: 94%
“…Earlier work from our laboratory showed that cardiac angiotensin II levels and oxidative stress are increased in diabetic male hearts (41, 43). These changes are reduced or absent in diabetic females (41)(42)(43). Earlier work from our laboratory also showed that in vivo treatment of male rats with an angiotensin-converting enzyme (ACE) inhibitor reduces or prevents diabetes-induced increase in angiotensin II and the resulting oxidative stress (41).…”
Section: Gender Differences In Conductionmentioning
confidence: 88%
See 1 more Smart Citation
“…For example, streptozotocin-induced diabetes depresses the rate of ventricular pressure development and prolongs the contraction and relaxation phases to a greater degree in papillary muscles from males than in those from females [12,28]. Also, in type 1 diabetic rats, the ventricular myocyte action potential is prolonged, corresponding to a decline in peak potassium currents in males but not in females [29,30]. Similar attenuation of peak potassium currents in males but not females is seen in ventricular myocytes from the db/db mouse model of type 2 diabetes with obesity [31], although whole-heart function is impaired to a similar degree in both sexes [32].…”
Section: Discussionmentioning
confidence: 99%
“…Chronically elevated ANG II attenuates K ϩ currents (57) and enhances oxidative stress (25), an important feature of diabetes (13,14). The involvement of ANG II in K ϩ current attenuation was suggested both by direct measurements of ANG II elevation (10,11,44) and by the fact that inhibition of either the angiotensin-converting enzyme (ACE) or blockade of ANG II receptors leads to augmentation of attenuated K ϩ currents (35,39) and associated channel proteins (42,43). Furthermore, relief of ANG II-mediated oxidative stress also augments these currents (41,56).…”
mentioning
confidence: 99%